STUDI GELOMBANG DI PERAIRAN SELATAN BALI MENGGUNAKAN MODEL SWAN - Rojali, Aditia
Wind generated waves in ocean is an important factor which is influenced human activity from offshore to nearshore. On nearshore water there are nonlinier factors that influence wave form. For studying nearshore waves, well-method to predict wave condition with nonlinier factors is needed and has good validation, economically accurate and fast. SWAN ( Simulating Waves Nearshore ) has been used widely in international wave study community. Therefore in this final project SWAN is used to study wave condition in Southern Bali Island. SWAN model is able to simulate generation by wind, propagation with refraction, and dissipation by whitecapping, depth induced breaking, dan bottom friction. Simulation has done with four different case time on February which is typically west monsoon condition using input from WAVEWATCH III model and NCEP reanalysis. Beside main simulation there were additional simulation to investigate wind sensitivity and to investigate dissipation factor that influenced wave field. High speed wind condition produce high wave condition. Dissipation contributor which has highest value to dissipate wave is wave blocking phenomena (64%) caused by coastline shape when input wave parameter is used for investigating dissipation factor. Comparison result show that SWAN has 0,26 RMS value for Young and Verhagen (1996) formula and 0,25 RMS value for Bretschneider (1984) formula.